ANALISA PEMBUATAN DAN KEKUATAN TARIK RENG BAJA TS 150 – R40.45 KASO METAL DI PT. TATALOGAM LESTARI - Ahcmad Fauzan (Jurnal Ilmiah Teknik, 2023)
In the process of making light steel lath type TS 150 – R40.45 metal rafters at PT. tatalogam lestari is done through a rolling process that goes through several processes. Starting from the provision of raw materials (coil), uncoiler process, roll forming process, roll stamp painting process, cutting process, quality control. All of these processes are interconnected to support production which in the end creates products according to standards and specifications. The steps in making battens include several processes, namely uncoiler to unroll the coil then with roll forming in the roll forming process to involve continuous folding of long strips of sheet metal into battens, then roll stamp, cutting process to get clearance and style. cut on the cutting machine, that is, clearance = 0.027 mm and cutting force = 69300 KN. finishing process, this process is carried out by checking (quality control), checking batten products whether there are defects in dimensions, defects in brand labels, physical material defects. Then the batten product will go to the repair division to be repaired and the product is ready to be packed.